Peran Manajemen Sumber Daya Manusia dalam Organisasi : Studi Kasus PT Telkom Indonesia - Arief Rachman Afandy; Zainul Abidin; Zainul Qudsi; Samsul Arifin; Syafiul Anam (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Human resource management (HRDM) is a crucial factor in supporting the success of companies in the digital era which is full of rapid change and global competition. Companies are required to not only adapt to technology, but also be able to build strategic and innovation-oriented MSDM systems. This study aims to examine the strategic role of MSDM in PT Telkom Indonesia (Persero) Tbk in supporting digital transformation and achieving organizational goals. Using a literature study approach, data was obtained from books, scientific journals, company annual reports, and official online sources. The results of the study show that PT Telkom Indonesia manages human resources strategically through various initiatives, such as the Great People Development Program (GPDP), digitization of the Human Capital Management (HCM) system, and strengthening the value-based work culture of